GTPase of the Immune-Associated Nucleotide Protein 5 Regulates the Lysosomal Calcium Compartment in T Lymphocytes - Serrano, Daniel; Ghobadi, Farnaz; Boulay, Guylain; Ilangumaran, Subburaj; Lavoie, Christine; Ramanathan, Sheela (Frontiers in Immunology, 2017)
T lymphocytes from Gimap5lyp/lyp rats carrying a recessive mutation in the GTPase of Immune-Associated Protein 5 (Gimap5) gene undergo spontaneous apoptosis. Molecular mechanisms underlying this survival defect are not yet clear. We have shown that Gimap5lyp/lyp T lymphocytes display reduced calcium influx following T cell antigen receptor (TCR) stimulation that was associated with impaired buffering of calcium by mitochondria. Here we investigated the subcellular localization of GIMAP5 and its influence on Ca2+ response in HEK293T cells and T lymphocytes. The more abundantly expressed GIMAP5v2 localizes to the lysosome and certain endosomal vesicles. Gimap5lyp/lyp T lymphocytes showed increased accumulation of calcium in the lysosomes as evidenced by Gly-Phe β-naphthylamide (GPN) triggered Ca2+ release. As a corollary, GPN-induced Ca2+ flux was decreased in HEK293T cells expressing GIMAP5v2. Strikingly, TCR stimulation of rat, mouse and human T lymphocytes increased lysosomal calcium content. Overall, our findings show that lysosomes modulate cellular Ca2+ response during T cell activation, and that GIMAP5 regulates the lysosomal Ca2+ compartment in T lymphocytes.